Detecting shock waves in non-fundamental mode RR Lyrae using large sample of spectra in SDSS and LAMOST - Xiao-Wei Duan; Xiao-Dian Chen; Li-Cai Deng; Fan Yang; Chao Liu; Anupam Bhardwaj; Hua-Wei Zhang
Steps toward the nature inside RR Lyrae variables can not only improve our understanding of variable stars but also innovate the precision when we use them as tracers to map the structure of the universe. In this work, we develop a hand-crafted one-dimensional pattern recognition pipeline to fetch out the "first apparitions", the most prominent observational characteristic of shock.We report the first detection of hydrogen emission lines in the first-overtone and multi-mode RR Lyrae variables. We find that there is an anti-correlation between the intensity and the radial velocity of the emission signal, which is possibly caused by opacity changing in the helium ionization zone. Moreover, we find one RRd star with hydrogen emission that possibly shows Blazhko-type modulations. According to our discoveries, with an enormous volume of upcoming data releases of variable stars and spectra, it may become possible to build up the bridge between shock waves and big problems like the Blazhko effect in non-fundamental mode RR Lyrae stars.
Keywords: Astronomy